2004
DOI: 10.1111/j.1365-2834.2004.00515.x
|View full text |Cite
|
Sign up to set email alerts
|

Use, misuse and non-use of health care assistants: understanding the work of health care assistants in a hospital setting

Abstract: The changing roles of registered nurses have direct implications for the roles of health care assistants: as registered nurses take on extra duties and responsibilities they are conceding some of their role to health care assistants. This has implications for nurse managers. The competence of health care assistants to carry out nursing work needs to be reassessed and there also needs to be ongoing monitoring and supervision of their work to maximize, and further develop, their contribution to patient care and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
109
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(118 citation statements)
references
References 16 publications
7
109
1
1
Order By: Relevance
“…26 For example, HCAs may be allocated technical tasks at times of increased workload and nurse shortage, but this work is withdrawn once professional staffing levels are restored. 27 HCAs have been found to exceed their remit by doing systematic observations and electrocardiogram tracings, 31 monitoring blood glucose levels without supervision, 28 taking blood and dressing wounds, 32 administering drugs while unsupervised, and running clinics without a nurse. 13 In addition to these high-level clinical tasks, they have been found to communicate with doctors, 29 and informally instruct nursing students and newlyqualified nurses.…”
Section: Healthcare Assistants In Hospital Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…26 For example, HCAs may be allocated technical tasks at times of increased workload and nurse shortage, but this work is withdrawn once professional staffing levels are restored. 27 HCAs have been found to exceed their remit by doing systematic observations and electrocardiogram tracings, 31 monitoring blood glucose levels without supervision, 28 taking blood and dressing wounds, 32 administering drugs while unsupervised, and running clinics without a nurse. 13 In addition to these high-level clinical tasks, they have been found to communicate with doctors, 29 and informally instruct nursing students and newlyqualified nurses.…”
Section: Healthcare Assistants In Hospital Settingsmentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29] The literature identifies the value of HCAs' contribution and a number of tensions and concerns around the nursing care skill mix. HCAs have been shown to provide practical nursing care such as bathing, 25,28,29 and emotional support, 25 freeing nurses to concentrate on therapeutic tasks, 26 medication, and paperwork.…”
Section: Healthcare Assistants In Hospital Settingsmentioning
confidence: 99%
“…33 Although the proximity to patients means that HCAs gather a lot of information about patients in their care, there are not always clear mechanisms to transfer knowledge from HCAs to nurses. 28,29 Schneider et al 27 also found evidence of variable communication between HCAs and the wider ward team about patient care, with HCAs feeling 'at risk' if they stepped outside the boundaries of their role.…”
Section: Introductionmentioning
confidence: 99%
“…27 Case studies 28 and observational data 29 suggest that HCA work in hospital is predominantly 'bedside' or involving routine technical tasks directly or indirectly related to patient care. Daykin and Clarke's observational study 30 of relationships between NHS hospital ward nurses and HCAs, identified a 'strongly hierarchical' organisation of care, with nurses having greater variety in their work, but often prevented from attending to patients by their responsibilities for administering medication and doing paperwork.…”
Section: The Clinical Support Workforcementioning
confidence: 99%
“…Research to date has looked mainly at comparisons between registered nurses and HCAs (Chang & Lam, 1998;Keeney, Hasson, McKenna, & Gillen, 2005;Pearcey, 2008;Workman, 1996) between student nurses and HCAs (Wakefield, 2000) or it has concentrated on describing HCA roles using case study approaches (Daykin & Clarke, 2000;James, Butler-Williams, Hunt, & Cox, 2010;Kessler et al, 2010;Spilsbury & Meyer, 2004). There is a need for more high quality research to generate knowledge to inform future development of the paid carer workforce, in order to maximise the benefits for patients and service users.…”
mentioning
confidence: 99%